Expression of the neurotransmitter-synthesizing enzyme glutamic acid decarboxylase in male germ cells. - Persson, H (1990)
The gene encoding glutamic acid decarboxylase (GAD), the key enzyme in the synthesis of the inhibitory neurotransmitter gamma-aminobutyric acid, is shown to be expressed in the testis of several different species. Nucleotide sequence analysis of a cDNA clone isolated from the human testis confirmed the presence of GAD mRNA in the testis. The major GAD mRNA in the testis was 2.5 kilobases. Smaller amounts of a 3.7-kilobase mRNA with the same size as GAD mRNA in the brain was also detected in the testis. In situ hybridization using a GAD-specific probe revealed GAD mRNA expressing spermatocytes and spermatids located in the middle part of rat seminiferous tubules. Studies on the ontogeny of GAD mRNA expression showed low levels of GAD mRNA in testes of prepubertal rats, with increasing levels as sexual maturation is reached, compatible with GAD mRNA expression in germ cells. In agreement with this, fractionation of cells from the rat seminiferous epithelium followed by Northern (RNA) blot analysis showed the highest levels of GAD mRNA associated with spermatocytes and spermatids. Evidence for the presence of GAD protein in the rat testis was obtained from the demonstration of GAD-like immunoreactivity in seminiferous tubules, predominantly at a position where spermatids and spermatozoa are found. Furthermore, GAD-like immunoreactivity was seen in the midpiece of ejaculated human spermatozoa, the part that is responsible for generating energy for spermatozoan motility.